Seizure frequency and patient‐centered outcome assessment in epilepsy. Issue 8 (5th June 2014) - Choi, Hyunmi; Hamberger, Marla J.; Munger Clary, Heidi; Loeb, Rebecca; Onchiri, Frankline M.; Baker, Gus; Hauser, W. Allen; Wong, John B.
Summary Objective Seizure frequency represents a commonly assessed epilepsy status, but in the context of the growing trend toward patient‐centered care, we examined the adequacy of seizure frequency as a measure of epilepsy status as perceived by the patient. Methods Between 2006 and 2008, we assessed seizure frequency, mood, and preference‐based health‐related quality of life (HRQOL) measured with the visual analog scale metric in 182 adult patients sampled consecutively. Using nonparametric tests and Monte Carlo computer simulations, we analyzed the relationship between preference‐based HRQOL and seizure frequency, and using regression analyses, we tested for significant predictors of preference‐based HRQOL. Results Only patients who had been seizure‐free for >1 year had significantly higher preference‐based HRQOL (p < 0.0001) than those who experienced any recurrent seizure, regardless of their seizure frequency. Among patients with recurrent seizures, preference‐based HRQOL and seizure frequency were not monotonically, linearly related. For patients with similar seizure frequency, preference‐based HRQOL varied substantially with large overlaps in preference‐based HRQOL across different seizure frequency categories. The Monte Carlo simulation found that seizure frequency was a poor predictor of preference‐based HRQOL about one third of the time. The presence of depressive symptoms was an independent predictor of preference‐based HRQOL measure, accounting for 33.5% of the variation in scores between patients. Significance Our findings highlight the importance of attaining complete seizure freedom and the substantial variation in preference‐based HRQOL among patients with similar seizure frequencies. To improve assessment of patient‐centered outcomes in epilepsy, we encourage adding direct measurement of preference‐based HRQOL into clinical care.. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.